Assessing role of LULC change in inducing UHI in Jaipur district, Rajasthan, India: A case study from 2009 – 2019 - Tanisha Ameriya; Udit Asopa; Charu Jhamaria (Songklanakarin Journal of Science and Technology (SJST), 2022)
The purpose of this study was to evaluate the decadal changes in the Land use/Land cover (LULC) pattern of the Jaipur district that affect the occurrence of Urban Heat Island (UHI) from 2009 to 2019, by using remote sensing and GIS data. The Landsat 7 and Landsat 8 datasets were classified using Supervised Maximum Likelihood classification method into classes: Urban, Vegetation, and Other. Further, using heatwave-based approach on land surface temperature (LST) maps, occurrence of UHI was determined. The results indicate a 26.55% increase in the urban area cover with a subsequent rise of 50C in the mean LST from year 2009 to 2019. With the increase in LULC and LST over the study period, intensification in the occurrence of Urban Heat Islands has been observed both in terms of their number and temperature. Interestingly, a 5.97% increase in vegetation cover has also been observed during the decade, but the effect of increase in vegetation was negligible and could not prevent the UHI effect in the area. Furthermore, Jaipur master development plan 2025 indicates expansion in terms of urbanisation and industrialization, so this study will be valuable for urban planners, policymakers, and relevant authorities in order to achieve sustainable development.